Quartz fiber silicon resin composite material thin-wall cylinder part and preparation method thereof
The preparation of quartz fiber silicone composite materials through vacuum-assisted RTM process solves the pores and glue problems of silicone/quartz fiber composites when preparing thin-walled cylinder specimens, improves the mechanical properties and ablation resistance of the material, reduces production costs, and is suitable for ram engine refueling chambers.
Patent Information
- Application Number
- CN202411635590.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The prior art is difficult to effectively solve the pores, glue defects and high cost problems of silicone resin/quartz fiber composites when preparing thin-walled cylinder specimens. Especially when used in ram engine refueling chambers, it cannot meet the requirements of high-temperature ablation resistance.
The vacuum-assisted RTM process is used to prepare quartz fiber silicone composite materials through vacuum injection, combining silicone resin and catalysts with specific components to ensure that the material cures under a vacuum environment, reduces pores and glue defects, and reduces production costs.
It significantly reduces pores and glue defects, improves the mechanical properties and ablation resistance of the material, reduces production costs, and enables it to be used in the refuel chamber of the ram engine.
Smart Images

Figure CN119773273A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of aerospace technology, and in particular to a quartz fiber silicone composite material thin-walled cylindrical part and a preparation method thereof. Background Art
[0002] At present, the development of the aerospace field is changing with each passing day, the upgrade cycle of ramjet engines is getting shorter and shorter, and the cost control is getting higher and higher. The afterburner of the ramjet engine works in an oxygen-rich environment and has a long working time, up to 600 seconds. Therefore, the thermal protection system of the afterburner chamber needs to provide corresponding conditions according to different thermal, structural and chemical environments. At the same time, the high-temperature ablation resistance of the insulation material in the ramjet engine is extremely high, but the insulation material does not adapt to the upgrade speed and cost control requirements of the ramjet engine, especially the high-temperature ablation resistance of the afterburner of the ramjet engine. This is related to whether the ramjet engine can maintain the predetermined flight attitude and orbit in the air. In order to meet the high-temperature erosion resistance requirements of the afterburner of the ramjet engine, it is necessary to improve manufacturing efficiency and reduce material costs.
[0003] Composite materials are a new type of material with the characteristics of high specific strength, specific modulus, low density and customizable design. They are widely used in aerospace, automobile manufacturing, medical equipment and other fields. Composite materials mainly include matrix materials and reinforcements. The matrix materials are divided into resin matrix, metal matrix and ceramic matrix. At present, resin matrix composite materials are widely used in the aerospace field. Silicone resin is a special type of resin material with a Q-type or T-type branched structure, and the core and skeleton are Si-O-Si molecular segments. In addition to excellent fluidity, low density, insulation and other characteristics, silicone resin often has high temperature resistance and low shrinkage. It has been widely used in the manufacture and processing of high-end materials such as medical devices, automobiles, additive manufacturing, aerospace, and has been continuously expanded to the modification of other types of non-silicon-based polymer materials. Quartz fiber is a fiber composed of quartz. Compared with commonly used carbon fiber, it has the characteristics of low thermal conductivity, high elongation at break, and good flexibility. Therefore, quartz fiber is widely used in the field of heat insulation.
[0004] Composite materials with silicone as the continuous phase and quartz fiber as the reinforcing material have been used in the aerospace field as special materials resistant to high temperature ablation. At present, silicone resin / quartz fiber composite materials often adopt compression molding process, which will have defects such as lack of glue and pores, which will lead to significant reduction in mechanical properties, ablation properties and stability performance. At the same time, the cost of the compression molding process is relatively high. The winding process is often used in the preparation of thin-walled cylindrical specimens, and the equipment cost required for this process is relatively high. Therefore, the pores, lack of glue and high cost of silicone resin / carbon fiber composite materials are still problems that need to be solved urgently, and it is necessary to solve product defects and molding problems from a process perspective. Summary of the invention
[0005] Based on the above, the purpose of the present invention is to provide a quartz fiber silicone composite thin-walled cylindrical part and a preparation method thereof, so as to solve the problem that the molding process cannot prepare thin-walled cylindrical specimens and the winding process has high cost, and the present invention is applied in the afterburner of a ramjet engine.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a quartz fiber silicone composite material thin-walled cylindrical part comprises the following steps:
[0008] Add silicone resin component A and silicone resin component B into the container according to the ratio, and stir evenly; add inhibitor, and mix evenly; finally, add catalyst, and mix evenly to obtain quartz fiber silicone composite material;
[0009] Degassing the quartz fiber silicone resin composite material until no bubbles are generated on the surface;
[0010] Install the quartz fiber preforms of different densities in the test mold and conduct mold closing, sealing and airtightness tests;
[0011] Using the RTM process, vacuum-injecting the quartz fiber silicone resin composite material into the test mold, and heating and curing;
[0012] Demolding the test mold after the injection of glue to obtain quartz fiber silicone resin composite material test pieces with different densities;
[0013] Testing the performance of the quartz fiber silicone composite material specimens of different densities to obtain quartz fiber silicone composite material specimens that meet the requirements, and determining the density of the target quartz fiber preform;
[0014] Installing the target quartz fiber preform in a thin-walled cylindrical mold, and performing mold closing, sealing and airtightness tests;
[0015] Using the RTM process, vacuum-injecting the quartz fiber silicone resin composite material into the thin-walled cylindrical mold, and heating and curing;
[0016] The thin-walled cylindrical mold after the injection of glue is demoulded to obtain a quartz fiber silicone resin composite material thin-walled cylindrical part.
[0017] As a preferred solution of a method for preparing a quartz fiber silicone resin composite thin-walled cylindrical member, the quartz fiber silicone resin composite material includes the following components in parts by mass:
[0018] Silicone resin component A 60 parts
[0019] Silicone resin B component 40-45 parts
[0020] Inhibitor 0.08-0.12 parts
[0021] Catalyst 0.04-0.08 parts;
[0022] The silicone resin A component includes vinyl terminated polydimethylsiloxane;
[0023] The silicone resin B component includes vinyl terminated polydimethylsiloxane and linear methyl hydrogen polysiloxane.
[0024] As a preferred solution for the preparation of a quartz fiber silicone composite thin-walled cylindrical part, the silicone resin B component is SH-VMQ silicone resin, specifically 5202N silicone oil type resin, with a resin content of 50%, a viscosity of 30,000 to 100,000 cP, an ethyl content of 0.5 to 1.5%, and an MQ ratio of 0.6 to 0.9.
[0025] As a preferred solution of a method for preparing a quartz fiber silicone composite thin-walled cylindrical member, the inhibitor comprises an acetylene alcohol compound; and the catalyst comprises a platinum-vinylsilane complex.
[0026] As a preferred embodiment of a method for preparing a quartz fiber silicone composite thin-walled cylindrical member, the target quartz fiber preform density is 0.25 g / cm 3 -0.35g / cm 3 .
[0027] As a preferred solution of the method for preparing a quartz fiber silicone composite thin-walled cylindrical part, during the air tightness test, the vacuum degree is -0.70 bar to -1.0 bar.
[0028] As a preferred solution of the method for preparing a quartz fiber silicone composite thin-walled cylindrical part, during the vacuum injection, the vacuum degree is -0.70 bar to -1.0 bar.
[0029] As a preferred solution of a method for preparing a quartz fiber silicone composite material thin-walled cylindrical part, the curing temperature is 120 to 160° C. and the curing time is 4 to 12 hours.
[0030] A quartz fiber silicone composite material thin-walled cylindrical part is prepared by any of the preparation methods described above.
[0031] An application of a quartz fiber silicone composite material thin-walled cylindrical part is based on the above-mentioned quartz fiber silicone composite material thin-walled cylindrical part, and the quartz fiber silicone composite material thin-walled cylindrical part is used in a ramjet engine afterburner.
[0032] The beneficial effects of the present invention are:
[0033] The present invention provides a quartz fiber silicone composite thin-walled cylindrical part and a preparation method thereof. The quartz fiber silicone composite material is prepared by a vacuum-assisted RTM process, which significantly reduces the pores of the test piece, solves defects such as lack of glue, and solves the problem that the molding process cannot prepare thin-walled cylindrical test pieces and the winding process has high cost. In addition, the mechanical properties, ablation resistance and stability of the material can be significantly enhanced, the production cost can be reduced, and it can be used in the afterburner of a ramjet engine. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the contents of the embodiments of the present invention and these drawings without paying any creative work.
[0035] Figure 1 The preparation flow chart of the quartz fiber silicone resin composite thin-walled cylindrical member of the present invention;
[0036] Figure 2 is an apparent mass diagram of a thin-walled cylindrical member made of quartz fiber silicone composite material prepared in Example 1 of the present invention;
[0037] Figure 3 is an apparent mass diagram of a thin-walled cylindrical member made of quartz fiber silicone composite material prepared in Example 2 of the present invention;
[0038] Figure 4 This is an apparent quality diagram of a thin-walled cylindrical part made of quartz fiber silicone composite material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0039] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.
[0040] This embodiment provides a method for preparing a quartz fiber silicone composite material thin-walled cylindrical part, comprising the following steps:
[0041] S100: adding silicone resin component A and silicone resin component B into a container according to the ratio, and stirring evenly; adding an inhibitor, and mixing evenly; and finally adding a catalyst, and mixing evenly to obtain a quartz fiber silicone composite material;
[0042] Specifically, the quartz fiber silicone composite material includes the following components in parts by mass: 60 parts of silicone resin component A, 40-45 parts of silicone resin component B, 0.08-0.12 parts of inhibitors, and 0.04-0.08 parts of catalysts; wherein the silicone resin component A includes vinyl-terminated polydimethylsiloxane; the silicone resin component B includes vinyl-terminated polydimethylsiloxane and linear methyl hydrogen polysiloxane, and the linear methyl hydrogen polysiloxane is used as a cross-linking agent. The silicone resin component B is SH-VMQ silicone resin, specifically 5202N silicone oil type resin, with a resin content of 50%, a viscosity of 30,000 to 100,000 cP, an ethyl content of 0.5 to 1.5%, and an MQ ratio of 0.6 to 0.9.
[0043] S200: degassing the quartz fiber silicone composite material until no bubbles are generated on the surface;
[0044] Specifically, the degassing process uses an oil-free vacuum pump to degas the quartz fiber silicone resin composite material until no bubbles are generated on the surface of the quartz fiber silicone resin composite material.
[0045] S300: Install quartz fiber preforms of different densities in the test mold to perform mold closing, sealing and airtightness tests;
[0046] Specifically, this embodiment uses quartz felts of different densities to prepare fiber preforms of different densities according to the size of 150mm×150mm×10mm, respectively. The fiber preforms are installed in a mold, which consists of an upper mold, a middle mold, and a lower mold. The glue inlet and the glue outlet are both set on the middle mold, wherein the glue inlet is connected to the glue inlet pipe through a manual ball valve, and the mold is locked with screws and nuts. Close the glue inlet ball valve, connect the glue outlet and the vacuum pump with a pneumatic hose, open the glue outlet ball valve, and then start the vacuum pump. The vacuum degree is set to -0.70bar~-1.0bar. When the vacuum degree reaches -1.0bar, the vacuum pump stops working and starts timing. If the vacuum pump does not work within 20 minutes (the vacuum degree is maintained at -0.70bar~-1.0bar), it means that the mold is airtight and the next step can be carried out.
[0047] S400: Using the RTM process, the quartz fiber silicone composite material is vacuum injected into the test mold and heated to cure;
[0048] Specifically, use a pressure barrel to perform the injection test, use a pneumatic hose to connect the pressure barrel and the test mold, the pressure barrel and the air source respectively, open all the ball valves on the test mold, adjust the pressure to 0.15MPa, and perform glue injection. When glue overflows from the test mold glue outlet, close the corresponding ball valve until all glue outlets overflow; then perform pressure maintenance and bubble removal. When two glue outlets overflow, close all the glue outlet ball valves to maintain the injection pressure for 10min to 20min, then open one of the glue outlet ball valves to remove bubbles until no bubbles are discharged, and close the ball valve without bubble discharge; perform the same operation on the other glue outlet ball valve, and after the bubble removal is completed, close all the glue outlet ball valves for pressure maintenance, the pressure maintenance time is 10min to 20min, and then perform bubble removal again. After two rounds of pressure maintenance and bubble removal, close all ball valves, disassemble all pipes, and place the test mold steadily in an oven for heating and curing, wherein the curing temperature is 120 to 160°C and the curing time is 4 to 12h. The curing temperature can be specifically set to 120° C., 140° C., or 160° C., and the curing time is 4 to 12 hours. The curing time can be specifically set to 4 hours, 8 hours, or 12 hours.
[0049] S500: demoulding the test mold after the injection of glue to obtain quartz fiber silicone composite material test pieces with different densities;
[0050] Specifically, the demoulding process removes the connecting bolts on the test mold, and demoulds the mold using the reverse screw holes to obtain the quartz fiber silicone composite material test piece.
[0051] S600: testing the performance of quartz fiber silicone composite material specimens of different densities, obtaining quartz fiber silicone composite material specimens that meet the requirements, and determining the density of the target quartz fiber preform;
[0052] Specifically, the hardness of the test plate was collected using a Shore D hardness tester; the quartz fiber silicone composite material specimen was then processed into a mechanical specimen and an oxyacetylene ablation specimen using a CNC machine tool, and the mechanical properties of the mechanical specimen and the oxyacetylene ablation properties of the oxyacetylene specimen were tested. A quartz fiber silicone composite material specimen with both excellent mechanical properties and ablation resistance was found, thereby determining the density of the target quartz fiber preform.
[0053] Specifically, when the oxyacetylene ablation performance of a thin-walled cylindrical part is directly measured, the cylindrical specimen requires the oxyacetylene sample to have a maximum diameter of 30 mm and a maximum thickness of 10 mm. Therefore, the thin-walled cylindrical part (inner diameter 116.5 mm, thickness 4.0 mm) prepared in this application does not meet the requirements for measuring the oxyacetylene ablation performance. It is necessary to first prepare a quartz fiber silicone composite material specimen to measure the relevant performance, determine the density of the target quartz fiber preform, and then use the target quartz fiber preform of this density to prepare a quartz fiber silicone composite material thin-walled cylindrical part.
[0054] S700: Install the target quartz fiber preform in a thin-walled cylindrical mold and perform mold closing, sealing and airtightness testing;
[0055] Specifically, the quartz felt is prepared according to the density of the target quartz fiber preform, the inner diameter is 116.5 mm, the thickness is 4.0 mm, and the length is 120 mm. The fiber preform is sleeved on the mandrel. The mold consists of an upper mold, a mandrel, a left lower mold, and a right lower mold. The glue inlet and the glue outlet are both set on the upper mold, wherein the glue inlet is connected to the glue inlet pipe through a manual ball valve, the mold is locked with screws and nuts, the glue inlet ball valve is closed, the glue outlet and the vacuum pump are connected with a pneumatic hose, the glue outlet ball valve is opened, and then the vacuum pump is started. The vacuum degree is set to -0.70 bar to -1.0 bar. When the vacuum degree reaches -1.0 bar, the vacuum pump stops working and starts timing. If the vacuum pump does not work within 10 to 20 minutes (the vacuum degree is maintained at -0.70 bar to -1.0 bar), it means that the mold is airtight and the next step can be carried out;
[0056] S800: Using RTM technology, the quartz fiber silicone composite material is vacuum injected into a thin-walled cylindrical mold and heated for curing;
[0057] Specifically, a pressure barrel is used for injection test, and a pneumatic hose is used to connect the pressure barrel and the thin-walled cylindrical mold, the pressure barrel and the air source respectively. All ball valves on the thin-walled cylindrical mold are opened, and the pressure is adjusted to 0.15MPa for injection. When the glue overflows from the glue outlet of the thin-walled cylindrical mold, the corresponding ball valve is closed until all the glue outlets overflow. Then, pressure maintenance and bubble removal are performed. When two glue outlets overflow, all the ball valves of the glue outlets are closed to maintain the injection pressure for 10min to 20min, and then one of the ball valves of the glue outlet is opened to discharge bubbles until no bubbles are discharged, and the ball valve without bubble discharge is closed. The same operation is performed on the other ball valve of the glue outlet. After the bubble removal is completed, all the ball valves of the glue outlet are closed for pressure maintenance. The pressure maintenance time is 10min to 20min, and the bubble removal is performed again. After two rounds of pressure maintenance and bubble removal are completed, all ball valves are closed, all pipes are disassembled, and the thin-walled cylindrical mold is steadily placed in an oven for heating and curing, wherein the curing temperature is 120 to 160°C and the curing time is 4 to 12h. The curing temperature can be specifically set to 120° C., 140° C., or 160° C., and the curing time is 4 to 12 hours. The curing time can be specifically set to 4 hours, 8 hours, or 12 hours.
[0058] S900: demoulding the thin-walled cylindrical mold after the injection of glue to obtain a quartz fiber silicone resin composite material thin-walled cylindrical part.
[0059] Specifically, the demoulding process removes the connecting bolts on the thin-walled cylindrical mold, and demoulds the mold using the reverse screw holes to obtain a quartz fiber silicone composite material thin-walled cylindrical part.
[0060] The present invention will be further described below by means of specific examples.
[0061] Example 1
[0062] Specimen 1: A quartz fiber silicone composite material specimen comprising:
[0063] 60 parts of silicone resin component A, 42 parts of silicone resin component B, 0.1 parts of inhibitor, 0.06 parts of catalyst;
[0064] The silicone resin component A is a vinyl-terminated silicone resin, the silicone resin component B is a vinyl-terminated silicone resin and a linear methyl hydrogen polysiloxane, the inhibitor is an acetylenic alcohol compound, and the catalyst is a platinum-vinyl silane complex. The density of the quartz fiber silicone composite material specimen is 0.3g / cm 3 .
[0065] A method for preparing a quartz fiber silicone composite material specimen:
[0066] Ingredients: Ingredients were prepared according to the requirements of the formula components. First, 180 g of silicone resin component A and 126 g of silicone resin component B were added to the container, and a disperser was used to stir the rubber materials to make them evenly mixed; then, 0.3 g of the inhibitor was added, and a disperser was used to mix the rubber materials evenly; finally, 0.18 g of the catalyst was added, and a disperser was used to mix the rubber materials evenly to obtain a quartz fiber silicone resin composite material.
[0067] Degassing: Use an oil-free vacuum pump to degas the quartz fiber silicone resin composite material until no bubbles are generated on the surface of the quartz fiber silicone resin composite material.
[0068] Mold closing and air tightness test: Quartz felt is made according to the density of 0.3g / cm 3 , 150mm×150mm×10mm in size, and the fiber preform is installed in a mold. The mold consists of an upper mold, a middle mold, and a lower mold. The glue inlet and the glue outlet are both set on the middle mold, wherein the glue inlet is connected to the glue inlet pipe through a manual ball valve, and the mold is locked with screws and nuts. Close the glue inlet ball valve, connect the glue outlet and the vacuum pump with a pneumatic hose, open the glue outlet ball valve, and then start the vacuum pump. The vacuum degree is set to -0.70bar~-1.0bar. When the vacuum degree reaches -1.0bar, the vacuum pump stops working and starts timing. If the vacuum pump does not work within 20min (the vacuum degree is maintained at -0.70bar~-1.0bar), it means that the mold is airtight and the next step can be carried out.
[0069] Injection: Use a pressure barrel to conduct the injection test, and use a pneumatic hose to connect the pressure barrel and the mold, and the pressure barrel and the air source. Open all ball valves on the mold, adjust the pressure to 0.15MPa, and inject glue. When glue overflows from the mold outlet, close the corresponding ball valve until all outlets overflow.
[0070] Pressure maintenance and bubble removal: When the two glue outlets overflow, close all the ball valves of the glue outlets to maintain the injection pressure for 10 to 20 minutes, then open one of the ball valves of the glue outlet to remove bubbles until no bubbles are discharged, and close the ball valve without bubble discharge; perform the same operation on the other ball valve of the glue outlet, and after the bubble removal is completed, close all the ball valves of the glue outlet to maintain the pressure for 10 to 20 minutes, and then remove the bubbles again. After two rounds of pressure maintenance and bubble removal, close all ball valves, disassemble all pipes, and place the mold steadily in the oven for heating and curing.
[0071] Curing: The curing temperature is 120-160°C and the curing time is 4-12h.
[0072] Demoulding: Remove the connecting bolts on the mould and use the reverse screw holes to demould to obtain the quartz fiber silicone composite material specimen.
[0073] Specimen 2: The preparation method of the quartz fiber silicone composite specimen is the same as that of specimen 1, but the density of the quartz felt is 0.4g / cm 3 .
[0074] Specimen 3: The preparation method of the quartz fiber silicone composite specimen is the same as that of specimen 1, but the density of the quartz felt is 0.5g / cm 3 .
[0075] Specimen 4: The preparation method of the quartz fiber silicone composite specimen is the same as that of specimen 1, but the density of the quartz felt is 0.6 g / cm 3 .
[0076] The hardness of the test plate of the quartz fiber silicone composite material specimens prepared by specimens 1-4 was collected using a Shore D hardness tester; the quartz fiber silicone composite material specimens were then processed into mechanical specimens and oxyacetylene ablation specimens using a CNC machine tool to test the mechanical properties of the mechanical specimens (GB / T528) and the oxyacetylene ablation properties of the oxyacetylene specimens (GJB323A). The mechanical properties test results and the oxyacetylene performance test results are shown in Table 1 and Table 2, respectively.
[0077] Table 1 Mechanical properties test results of quartz fiber silicone composite specimens
[0078]
[0079] Table 2 Oxyacetylene ablation performance parameters of quartz fiber silicone composite specimens
[0080]
[0081]
[0082] From Table 1 and Table 2, it can be seen that with the increase of quartz felt density, the tensile strength first increases and then decreases, and the elongation at break shows an increasing law as a whole; at the same time, with the increase of quartz felt density, the material density gradually increases, and the line ablation rate gradually increases. When the density of quartz felt is too low, the strength of the specimen is low. Therefore, when the density of quartz felt is 0.3g / cm 3 When (density error ± 0.05g / cm 3 , the density is 0.25g / cm 3 -0.35g / cm 3 ), the prepared quartz fiber silicone composite material specimen has the highest density, the lowest linear ablation rate, the most excellent ablation resistance, and also has excellent mechanical properties. It is used to prepare quartz fiber silicone composite thin-walled cylindrical parts to meet the application requirements in the afterburner of ramjet engines.
[0083] A method for preparing a quartz fiber silicone resin composite thin-walled cylindrical part:
[0084] The components of the quartz fiber silicone composite material specimen are consistent with those of specimen 1, but the process conditions of the preparation process are inconsistent. A quartz fiber silicone composite material thin-walled cylindrical part is mainly prepared.
[0085] Ingredients: Ingredients were prepared according to the requirements of the formula components. First, 360 g of silicone resin component A and 252 g of silicone resin component B were added to the container, and a disperser was used to stir the rubber materials to make them evenly mixed; then, 0.6 g of inhibitor was added, and a disperser was used to mix the rubber materials evenly; finally, 0.36 g of catalyst was added, and a disperser was used to mix the rubber materials evenly to obtain a quartz fiber silicone resin composite material.
[0086] Degassing: Use an oil-free vacuum pump to degas the quartz fiber silicone resin composite material until no bubbles are generated on the surface of the quartz fiber silicone resin composite material;
[0087] Mold closing and air tightness test: Quartz felt is made according to the density of 0.3g / cm 3, an inner diameter of 116.5 mm, a thickness of 4.0 mm, and a length of 120 mm are prepared into a fiber preform, and the fiber preform is sleeved on the mandrel. The mold consists of an upper mold, a mandrel, a left lower mold, and a right lower mold. The glue inlet and the glue outlet are both set on the upper mold, wherein the glue inlet is connected to the glue inlet pipe through a manual ball valve, the mold is locked with screws and nuts, the glue inlet ball valve is closed, the glue outlet and the vacuum pump are connected with a pneumatic hose, the glue outlet ball valve is opened, and then the vacuum pump is started, the vacuum degree is set to -0.70 bar to -1.0 bar, and the vacuum pump stops working and starts timing when the vacuum degree reaches -1.0 bar. If the vacuum pump does not work within 10 to 20 minutes (the vacuum degree is maintained at -0.70 bar to -1.0 bar), it means that the mold is airtight and the next step can be carried out;
[0088] Injection: Use a pressure barrel to conduct the injection test, and use a pneumatic hose to connect the pressure barrel and the mold, the pressure barrel and the air source, the mold and the vacuum pump. Open all the ball valves on the mold, adjust the pressure to 0.15MPa, and inject glue. The vacuum degree of the mold cavity is maintained at -0.70bar~-1.0bar. When glue overflows from the mold outlet, close the corresponding ball valve and remove the vacuum assistance until all the outlets overflow.
[0089] Pressure maintenance and bubble removal: When the two glue outlets overflow, close all the ball valves of the glue outlets to maintain the injection pressure for 15 minutes, then open one of the ball valves of the glue outlets to remove bubbles until no bubbles are discharged, and close the ball valve without bubble discharge; perform the same operation on the other ball valve of the glue outlet, and after the bubble removal is completed, close all the ball valves of the glue outlets to maintain the pressure for 15 minutes, and then remove the bubbles again. After two rounds of pressure maintenance and bubble removal, close all ball valves, disassemble all pipes, and place the mold steadily in the oven for heating and curing.
[0090] Curing: Curing temperature is 150℃, curing time is 6h;
[0091] Demoulding: Remove the connecting bolts on the mould and use the reverse screw holes to demould to obtain a quartz fiber silicone composite thin-walled cylindrical part.
[0092] Example 2
[0093] A method for preparing a quartz fiber silicone resin composite thin-walled cylindrical part:
[0094] The test process of the specimen is consistent with that of Example 1, and the direct use density is 0.3g / cm 3 The quartz felt is prepared in accordance with the preparation process of the quartz fiber silicone composite material thin-walled cylindrical member prepared in Example 1, but the raw material components of the specimen prepared in Example 1 are inconsistent.
[0095] The components of a quartz fiber silicone composite material specimen include:
[0096] 60 parts of silicone resin component A, 40 parts of silicone resin component B, 0.08 parts of inhibitor, 0.08 parts of catalyst;
[0097] The quartz fiber silicone resin composite material is prepared by first adding 360g of silicone resin component A and 240g of silicone resin component B into a container, and using a disperser to stir to mix the rubber evenly; then adding 0.48g of inhibitor, and using a disperser to mix the rubber evenly; finally adding 0.48g of catalyst, and using a disperser to mix the rubber evenly to obtain a quartz fiber silicone resin composite material.
[0098] Example 3
[0099] A method for preparing a quartz fiber silicone resin composite thin-walled cylindrical part:
[0100] The test process of the specimen is consistent with that of Example 1, and the direct use density is 0.3g / cm 3 The quartz felt is prepared in accordance with the preparation process of the quartz fiber silicone composite material thin-walled cylindrical member prepared in Example 1, but the raw material components of the specimen prepared in Example 1 are inconsistent.
[0101] The components of a quartz fiber silicone composite material specimen include:
[0102] 60 parts of silicone resin component A, 45 parts of silicone resin component B, 0.12 parts of inhibitor, 0.04 parts of catalyst;
[0103] The quartz fiber silicone resin composite material is prepared by first adding 360g of silicone resin component A and 270g of silicone resin component B into a container, and using a disperser to stir the rubber material to mix evenly; then adding 0.72g of an inhibitor, and using a disperser to mix the rubber material evenly; finally adding 0.24g of a catalyst, and using a disperser to mix the rubber material evenly to obtain a quartz fiber silicone resin composite material.
[0104] In order to further illustrate the key points of this patent, comparative examples are added for illustration.
[0105] Comparative Example 1
[0106] Consistent with the preparation process and raw material components of Example 1, during the preparation of the quartz fiber silicone composite thin-walled cylindrical part, when the glue is injected, the inner cavity of the mold is connected to the atmosphere and is not carried out in a vacuum environment.
[0107] The apparent mass of the thin-walled cylindrical pieces of quartz fiber silicone composite material prepared in Examples 1-3 and Comparative Example 1 was collected using a digital camera. The apparent mass of the thin-walled cylindrical pieces prepared in the examples is as follows: Figure 2 and Figure 3As shown, the apparent quality of the thin-walled cylindrical part prepared in Comparative Example 1 is as follows Figure 4 As shown in the figure, Figure 2 and Figure 3 The surface of medium and thin-walled cylindrical parts is smooth and tidy, without any glue defects. Figure 3 There are dry spots and glue deficiency on the surface of the thin-walled cylindrical parts. This defect may be caused by air inclusion. Therefore, it is necessary to provide a vacuum environment in the mold cavity (during the injection process) to prevent glue deficiency defects from occurring in the sample.
[0108] The quartz fiber silicone composite material thin-walled cylindrical part prepared in Example 1 was processed into the design required size using a CNC machine tool.
[0109] The length, inner diameter, thickness and step size of the test piece obtained after processing are checked with a vernier caliper. Among them, the length dimension is tested in four quadrants evenly distributed along the circumference, the inner diameter is tested at 4 points in each of the two openings (evenly distributed in four quadrants), the thickness test position is consistent with the inner diameter test point (a total of 8 points), the step height is tested at 4 points (evenly distributed in four quadrants along the circumference), and the step outer diameter measurement point is the same as the step height (a total of 4 points). The design requirements and test values of the specific test pieces are shown in Table 3. All meet the standards.
[0110] Table 3 Dimensional data of thin-walled cylindrical parts made of quartz fiber silicone composite materials
[0111]
[0112]
[0113] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.
Claims
1. A method for preparing a quartz fiber silicone composite thin-walled cylindrical part, characterized in that: The following steps are involved: Add silicone resin component A and silicone resin component B into the container according to the ratio, and stir evenly; add inhibitor, and mix evenly; finally, add catalyst, and mix evenly to obtain quartz fiber silicone composite material; Degassing the quartz fiber silicone resin composite material until no bubbles are generated on the surface; Install the quartz fiber preforms of different densities in the test mold and conduct mold closing, sealing and airtightness tests; Using the RTM process, vacuum-injecting the quartz fiber silicone resin composite material into the test mold, and heating and curing; Demolding the test mold after the injection of glue to obtain quartz fiber silicone resin composite material test pieces with different densities; Testing the performance of the quartz fiber silicone composite material specimens of different densities to obtain quartz fiber silicone composite material specimens that meet the requirements, and determining the density of the target quartz fiber preform; Installing the target quartz fiber preform in a thin-walled cylindrical mold, and performing mold closing, sealing and airtightness tests; Using the RTM process, vacuum-injecting the quartz fiber silicone resin composite material into the thin-walled cylindrical mold, and heating and curing; The thin-walled cylindrical mold after the injection of glue is demoulded to obtain a quartz fiber silicone resin composite material thin-walled cylindrical part.
2. The method for preparing a quartz fiber silicone composite thin-walled cylindrical part according to claim 1, characterized in that: The quartz fiber silicone resin composite material includes the following components in parts by mass: Silicone resin component A 60 parts The silicone resin A component includes vinyl terminated polydimethylsiloxane; The silicone resin B component includes vinyl terminated polydimethylsiloxane and linear methyl hydrogen polysiloxane.
3. The method for preparing a quartz fiber silicone composite thin-walled cylindrical part according to claim 2, characterized in that: The silicone resin component B is SH-VMQ silicone resin, specifically 5202N silicone oil type resin, with a resin content of 50%, a viscosity of 30000-100000 cP, an ethyl content of 0.5-1.5%, and an MQ ratio of 0.6-0.
9.
4. The method for preparing a quartz fiber silicone composite thin-walled cylindrical part according to claim 1, characterized in that: The inhibitor comprises an acetylene alcohol compound; and the catalyst comprises a platinum-vinylsilane complex.
5. The method for preparing a quartz fiber silicone composite material thin-walled cylindrical part according to claim 1, characterized in that: The target quartz fiber preform density is 0.25 g / cm 3 -0.35g / cm 3 .
6. The method for preparing a quartz fiber silicone composite material thin-walled cylindrical part according to claim 1, characterized in that: During the air tightness test, the vacuum degree is -0.70 bar to -1.0 bar.
7. The method for preparing a quartz fiber silicone composite material thin-walled cylindrical part according to claim 1, characterized in that: During the vacuum injection, the vacuum degree is -0.70 bar to -1.0 bar.
8. The method for preparing a quartz fiber silicone composite material thin-walled cylindrical part according to claim 1, characterized in that: The curing temperature is 120-160° C., and the curing time is 4-12 hours.
9. A quartz fiber silicone composite thin-walled cylindrical part, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. An application of a quartz fiber silicone composite thin-walled cylindrical part, based on the quartz fiber silicone composite thin-walled cylindrical part according to claim 9, characterized in that: The quartz fiber silicone resin composite material thin-walled cylindrical part is used in the afterburner chamber of a ramjet engine.
Citation Information
Patent Citations
Silicone resin composites for high temperature durable elastic composite applications and methods for fabricating same
CN101903429A
Composite heatproof bearing cylinder and preparation method thereof
CN102729482A
Method for manufacturing resin transfer molding (RTM) carbon fiber composite test blocks
CN105415711A
Preparation method of silicon resin composite material capable of improving high temperature resistance
CN114044931A
Silicon-containing aryne resin / quartz fiber composite material as well as preparation method and application thereof
CN116041757A